Photophysical Behavior of Modified Xanthenic Dyes Embedded into Silsesquioxane Hybrid Films: Application in Photooxidation of Organic Molecules - Carolina V. Waiman; Rodrigo E. Palacios; Hernán A. Montejano; Carlos A. Chesta; María Lorena Gómez (International Journal of Photoenergy)
Polymeric materials based on a bridged silsesquioxane with pendant dodecyl chains were synthesized and modified with different xanthenic dyes with the aim of developing a material with potential application in photooxidation of organic compounds. The employed dyes constitute a family of novel xanthenic chromophores with outstanding properties as singlet oxygen photosensitizers. The hybrid matrix was chosen for its enhanced properties such as flexibility and chemical resistance. The employed dyes were easily incorporated into the hybrid polymer obtaining homogeneous, transparent, and low-refractive-index materials. The polymeric films were characterized using UV-Vis absorption, fluorescence, and laser flash photolysis techniques. The ability of these materials to produce singlet oxygen was tested following the photooxidation of 9,10-dimethylanthracene which is a well-known chemical trap for singlet oxygen. High photooxidation efficiencies were observed for these materials, which present the advantage of being easily removed/collected from the solution where photooxidation takes place. While photobleaching of the incorporated dyes is commonly observed in the solution, it takes place very slowly when dyes are embedded in the hybrid matrix. These properties bode well for the potential use of these materials in novel wastewater purification strategies.